SOCIUS CLASH OF CHAMPIONS: SOCIOLOGY LEARNING MEDIA INNOVATION FOR CLASS XI SPECIAL TALENT MAN 1 MALANG - Saputra, Indra Fagil (Educational Technology Journal, 2025)
Technological developments play an important role in the learning process of the modern era. Sociology learning in schools has a significant role in shaping the character of students because it is a fundamental aspect that produces social change. Class XI special talent MAN 1 Malang has kinesthetic student characteristics. Researchers innovated Team Games Tournament (TGT) based learning based on sociology material on social problems by developing the Clash of Champions concept. The research used qualitative research methods with descriptive methods, data collection techniques used by researchers to obtain data through interviews, observation, and documentation. By conducting interviews with 4 students of class XI F special talent for sports and 1 sociology subject teacher as the sociology subject teacher in the study group of class XI MAN 1 Malang in 2024/2025. Socius Clash of Champions innovation provides space for students with kinesthetic learning styles where this concept combines 2 learning media, namely Puzzlemaker and Wordwall. The concept of Socius Clash of Champions is in line with the view of constructivism theory where students build skills and knowledge independently, educators act as facilitators with interesting learning designs to form Student Centered Learning (SCL).